Characteristics of the tree shrew humoral immune system. (November 2020) - Zhang, Jingjing; Xiao, Hongjian; Bi, Yanwei; Long, Qiong; Gong, Yue; Dai, Jiejie; Sun, Ming; Cun, Wei
Highlights: This research analyzed the antibody types in tree shrews, and preliminarily established a humoral immune detection system. The tree shrew does not encode an IgD antibody; however, its IgM antibody has the highest homology with primates. The kinetic process of the immune response in tree shrews is somehow different compared to mice. Abstract: Preclinical studies require an immune response similar to that of humans in a small animal model that is convenient to operate. Based on genome alignment, tree shrews are small animals considered to be more similar to primates than are rodents, and many human disease models have been established with tree shrews. However, the characteristics of the humoral immune response of tree shrews remain to be elucidated. In this study, the genetic sequence of the heavy chain constant region of tree shrew immunoglobulin (Ig) was complemented, and the results of immunoglobulin domain homology and transcriptome analysis showed that the tree shrew genome encodes only four classes of antibodies and does not encode IgD. The oldest IgM antibody has the highest homology with primates. After the complete sequence of each type of antibody was obtained, the tree shrew antibody protein was further expressed and purified by in vitro recombination, and an IgG quantitative evaluation system was established. The highly effective immuno protective effect induced by HSV-1 infection and the significant bactericidal effect induced by Neisseria meningitidis group C polysaccharide immunization showed that tree shrews exhibited immune responses more similar to humans than to mice. This may provide better predictive value for vaccine preclinical research.